Correlation between morphological, structural and electrical properties of graphite and exfoliated graphene nanostructures. (January 2020) - Rezaei, Asma; Kamali, Bita; Kamali, Ali Reza
Graphical abstract: Highlights: Pure graphite electrodes were exfoliated into graphene powders by three methods. Structure and morphology of graphene powders produced were evaluated. Electrical performance of the graphene powders was evaluated under various pressures. Specific electrical conductivity is an effective tool for conductivity evaluations. Molten salt exfoliated graphene nanosheets exhibit a high SEC of 26.4 S cm 2  g −1 . Abstract: The bulk electrical conductivity of graphene powders plays a key role in designing new graphene-based materials with enhanced properties for a variety of functional and structural applications. Despite its importance, however, the electrical characterization of graphene powders is not well defined in the literature. This study is aimed to shed light on this underexplored and important area. Two different exfoliation strategies were employed to exfoliate an ultra-high purity graphite, i.e. room temperature mechanical exfoliation and high-temperature molten salt exfoliation. The morphology and structural characteristics of the graphene powders were analysed by various techniques. Also, the electrical properties of the powders were evaluated at various pressures using a custom-made powder compression device. For the first time, we propose specific electrical conductivity (SEC) as an effective tool to express bulk electrical properties, by which a correlation between the microstructure and structural characteristics of graphene powders and their electrical performance could be developed.